Carboxymethyl cellulose coated Fe3O4@SiO2 core–shell magnetic nanoparticles for methylene blue removal: equilibrium, kinetic, and thermodynamic studies. Issue 1 (January 2018) - Zirak, Maryam; Abdollahiyan, Aysan; Eftekhari-Sis, Bagher; Saraei, Mahnaz
Abstract Fe3 O4 @SiO2 core–shell magnetic nanoparticles (MNPs) were prepared by chemical coprecipitation of FeCl3 ·6H2 O and FeCl2 ·4H2 O in alkaline solution, followed by silylation using triethoxy silane, and then by treatment with 3-aminopropyltriethoxysilane. The corresponding MNPs were coated with carboxymethyl cellulose (CMC) by amide formation between carboxyl groups of CMC and amine functional groups of nanoparticles. The structure of MNPs was characterized by FT-IR, SEM, EDX, TEM, XRD, VSM and TGA analysis. CMC-coated Fe3 O4 @SiO2 magnetic nanoparticles were used as an efficient adsorbent for the removal of methylene blue (MB, a cationic dye) from aqueous solutions. The impact of various factors such as adsorbent dosage, pH, initial concentration of MB, temperature and contact time were investigated. The kinetic, isotherms, and thermodynamic parameters of adsorption were also studied.